2020
DOI: 10.1016/j.brs.2019.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar repetitive transcranial magnetic stimulation (rTMS) for essential tremor: A double-blind, sham-controlled, crossover, add-on clinical trial

Abstract: Background: There is controversial evidence about the effect of cerebellar low-frequency stimulation in patients with essential tremor (ET). Objectives: In this study we assessed safety and effectiveness of 1 Hz (low-frequency) cerebellar repetitive transcranial magnetic stimulation (rTMS) on tremor severity in patients with essential tremor in a sham-controlled crossover trial. Methods: A total of 23 patients assigned into two groups to receive either sham (n ¼ 10) or rTMS (n ¼ 13) treatment, with crossing ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 45 publications
3
21
0
Order By: Relevance
“…This study also demonstrated restoration of CTC connectivity on the fMRI (38). However, two other low frequency rTMS studies with a similar 5day paradigm found no significant difference between active and sham stimulation conditions (41,42).…”
Section: Therapeutic Use Of Rtmssupporting
confidence: 56%
“…This study also demonstrated restoration of CTC connectivity on the fMRI (38). However, two other low frequency rTMS studies with a similar 5day paradigm found no significant difference between active and sham stimulation conditions (41,42).…”
Section: Therapeutic Use Of Rtmssupporting
confidence: 56%
“…Also, the size of the cerebellum renders specific stimulation of certain parts problematic. The exact stimulation regions are not specified in many studies 50,72,77,[80][81][82][83] . Also, certain measurements such as CBI cannot be elicited in every person, or are not tolerated, so that these participants had to be excluded in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…To induce plasticity, we used procedures previously described to be effective in inducing plasticity in the cerebellum. In experiment 1, 1 Hz rTMS 50 , PAS 17 , cTBS 44,51 , and anodal tDCS [64][65][66] was used. 1 Hz rTMS was administered with 90% RMT for 20 min using a Magstim Rapid magnetic stimulator (Magstim Company, Whitland, Dyfed, UK) 50 .…”
Section: Transcranial Magnetic Stimulation Single-and Multi-pulse Tmmentioning
confidence: 99%
See 1 more Smart Citation
“…Various types of non-invasive central stimulation may provide further treatment options for essential tremor. Trans cranial magnetic stimulation of the cerebellum has been studied in a small number of patients, and demonstrates acute motor improvement in essential tremor; however, not all studies have shown significant improvements compared to sham stimulation and whether long-lasting improvements can occur is uncertain [ 61 ], [ 62 ]. Another form of central stimulation, trans cranial direct current stimulation has shown a significant improvement in TETRAS scores in 6 essential tremor patients after a 15 session treatment course spanning across a 50 day period [ 63 ].…”
Section: Novel Interventions For Essential Tremormentioning
confidence: 99%